2015
DOI: 10.1016/j.athoracsur.2015.01.064
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Lobectomy for Non-Small Cell Lung Cancer After Definitive Radiation Treatment

Abstract: Background Salvage surgical resection for non-small cell lung cancer (NSCLC) patients initially treated with definitive chemotherapy and radiation can be performed safely, but the long-term benefits are not well characterized. Methods Perioperative complications and long-term survival of all patients with NSCLC who received curative-intent definitive radiation with or without chemotherapy followed by lobectomy from 1995-2012 were evaluated. Results During the study period, 31 patients met inclusion criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 17 publications
0
44
0
Order By: Relevance
“…8) Yang et al also showed that the median PFS and OS were 10.3 and 32.5 months, respectively. 18) These results indicate that salvage lung resection after definitive chemoradiation is feasible, with an encouraging survival. The median recurrence-free survival (RFS) after surgery was reported to be just 6 months after response to gefitinib administration.…”
Section: Event-free Survivalmentioning
confidence: 65%
See 1 more Smart Citation
“…8) Yang et al also showed that the median PFS and OS were 10.3 and 32.5 months, respectively. 18) These results indicate that salvage lung resection after definitive chemoradiation is feasible, with an encouraging survival. The median recurrence-free survival (RFS) after surgery was reported to be just 6 months after response to gefitinib administration.…”
Section: Event-free Survivalmentioning
confidence: 65%
“…Eventually, eleven papers (cases series) including various treatment methods before salvage surgery were identified ( Table 2). [8][9][10][11][12][13][14][15][16][17][18] These studies were all retrospective in nature and performed at a single institution. Furthermore, there were imbalances in the patients' characteristics that cannot be excluded due to the small number of patients.…”
Section: Accumulation Of Scientific Knowledgementioning
confidence: 99%
“…In addition, the existence of viable tumor cells was supported with PET-CT, thus biopsy wasn't considered necessary. The rates of pneumonectomy in studies including more than 20 patients are 42-59% (3)(4)(5). Because of the location of recurrent disease in our case, RP was applied.…”
Section: Discussionmentioning
confidence: 93%
“…There are few published data about surgery after radical CRT. In these studies, low survival, high morbidity and mortality rates are usually reported (3)(4). Salvage surgery has been generally investigated in retrospective series.…”
Section: Discussionmentioning
confidence: 99%
“…Uramoto stated that salvage thoracic operations, in a wide sense, can be defined as surgical resection of persistent or recurrent primary lung tumors after previous treatments, in addition to urgent matters such as hemoptysis 1) . Some reports have indicated that salvage thoracic operations after definitive chemoradiation are feasible with an encouraging survival rate, as the median progression-free survival (PFS) was 10.3-12 months with an overall survival (OS) of 30-32.5months 2,3) . Such surgery might therefore be considered a favorable treatment option for select patients.…”
Section: Discussionmentioning
confidence: 99%